2020
DOI: 10.1111/jpi.12682
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms and obesity: Timekeeping governs lipid metabolism

Abstract: Almost all living organisms have evolved autoregulatory transcriptional‐translational feedback loops that produce oscillations with a period of approximately 24‐h. These endogenous time keeping mechanisms are called circadian clocks. The main function of these circadian clocks is to drive overt circadian rhythms in the physiology of the organisms to ensure that main physiological functions are in synchrony with the external environment. Disruption of circadian rhythms caused by genetic or environmental factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 124 publications
1
75
0
3
Order By: Relevance
“…The homeostasis of BAs pool is maintained by enterohepatic cycle. Quantitative determination of BAs profiles via UPLC-MS analysis could reflect the enterohepatic circulation of BAs (35,36). In our study, we observed great changes in BA composition of serum, ileal digesta, and liver, which might ascribe ileal microbiota modification with L. delbrueckii.…”
Section: Figure 7 |mentioning
confidence: 53%
“…The homeostasis of BAs pool is maintained by enterohepatic cycle. Quantitative determination of BAs profiles via UPLC-MS analysis could reflect the enterohepatic circulation of BAs (35,36). In our study, we observed great changes in BA composition of serum, ileal digesta, and liver, which might ascribe ileal microbiota modification with L. delbrueckii.…”
Section: Figure 7 |mentioning
confidence: 53%
“…The GIT is the most heavily colonized organ and comprises various sections with different environmental conditions and microbial profiles. The microbiota in the GIT is associated with a broad range of functions within the host, including the fermentation of complex macronutrients, nutrient and vitamin production, cellulose fermentation, protection from pathogens, maintenance of the balance of the immune system, and physiological metabolism in distal organs or tissues ( Han et al., 2018 ; Li et al., 2020 ; Yin et al., 2018 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Findings linking circadian disorders and obesity are becoming more and more popular [21]. Our ndings suggested that altered light/dark cycle resulted in the weight gain in db/db mice.…”
Section: Discussionmentioning
confidence: 74%